An improved MPPT algorithm to minimize transient and steady state oscillation conditions for small SPV systems - Kashif Javed; Haroon Ashfaq; Rajveer Singh (International Journal of Renewable Energy Development, 2018)
Small solar PV systems mostly residential PV systems are bounded to be low cost. So these systems are required low-cost processors, and these low-cost processors can only process simple algorithm efficiently. The conventional P&O MPPT algorithm is widely employed algorithm to control solar PV systems because of its simplicity, low cost, and ease of implementation. During rapid radiation change condition (RRC) the output voltage of conventional P&O MPPT algorithm is found unstable and suffers oscillations around MPP at transient and steady state conditions. This paper proposes a simple MPPT algorithm for small or residential solar PV systems to eliminate such above said drawbacks. The proposed MPPT controls the step size (dD) of the boost converter duty cycle (D) according to the system input conditions and have the ability to compensate the transient as well as steady-state oscillations around MPP and stabilize the output voltage under RRC and variable load conditions. To validate the proposed algorithm, a 1kW photovoltaic system model is simulated using MATLAB/Simulink, and the performance of the system is also investigated under RRC. The performance of proposed MPPT algorithm is found to be adequate under various insolation patterns. An experimental set-up comprising a boost converter, solar emulator with dSPACE controller is also used to investigate the performance of proposed MPPT algorithm further.Article History: Received October 4th 2017; Received in revised form September 15th 2018; Accepted November 1st 2018; Available onlineHow to Cite This Article: Javed, K. Ashfaq, H and Singh, R. (2018). An Improved MPPT Algorithm to Minimize Transient and Steady State Oscillation Conditions for Small SPV Systems. International Journal of Renewable Energy Development, 7(3), 191-197.http://dx.doi.org/10.14710/ijred.7.3.191-197